1977
DOI: 10.1172/jci108856
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-mediated platelet aggregation. Evidence for multivalent interactions of intermediate specificity between collagen and platelets.

Abstract: A B S T R A C T We have shown previously that periodate oxidation ofcollagen carbohydrate does not affect its ability to aggregate platelets. We now describe an additional characterization of periodate-modified collagen which demonstrates that collagen devoid of intact carbohydrate is fully capable of fibril formation, and we confirm its capacity to initiate platelet aggregation. Furthermore, we demonstrate that the platelet aggregating abilities of Types I, II, and III fibrillar collagen are quite similar des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0
1

Year Published

1978
1978
1998
1998

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 34 publications
1
23
0
1
Order By: Relevance
“…Santoro and Cunningham (8) have recently proposed that adhesion of platelets to collagen and their subsequent aggregation result from-the interaction of multiple binding sites on the platelet surface, which may exhibit only modest affinity in the monovalent state for some'structural feature of the collagen molecule also multiply present in the collagen fibril. This concept is consistent with the similar capacities of the genetically distinct collagen types (8,12,13), including the (aI)3 trimer (14), to initiate aggregation provided they are in a fibrillar form. This occurs despite the existence of regions of variation in amino acid sequence and different polypeptide chain compositions and may suggest that completely identical platelet binding sites are'not present on the surface of these different collagen fibers.…”
supporting
confidence: 81%
See 3 more Smart Citations
“…Santoro and Cunningham (8) have recently proposed that adhesion of platelets to collagen and their subsequent aggregation result from-the interaction of multiple binding sites on the platelet surface, which may exhibit only modest affinity in the monovalent state for some'structural feature of the collagen molecule also multiply present in the collagen fibril. This concept is consistent with the similar capacities of the genetically distinct collagen types (8,12,13), including the (aI)3 trimer (14), to initiate aggregation provided they are in a fibrillar form. This occurs despite the existence of regions of variation in amino acid sequence and different polypeptide chain compositions and may suggest that completely identical platelet binding sites are'not present on the surface of these different collagen fibers.…”
supporting
confidence: 81%
“…This occurs despite the existence of regions of variation in amino acid sequence and different polypeptide chain compositions and may suggest that completely identical platelet binding sites are'not present on the surface of these different collagen fibers. The inability of monomeric collagen to inhibit aggregation induced by the identical collagen in fibrillar form (8) further supports this model. Fibronectin, a collagen-binding protein with molecular weight of 440,000 composed of two 220,000-dalton polypeptide chains (15), is found in plasma and on the surface of various cells and has been implicated in the adhesion of fibroblasts to collagenous substrates (16,17).…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…(8) have shown that only denatured collagen can act as a substrate for the platelet glucosyl transferase, whereas only native, fibrous collagen serves as a platelet substrate in the collagen-platelet interaction (9,10). In addition, others have shown that the carbohydrate residues of collagen can be completely destroyed by periodate oxidation without affecting the ability of the fibrous form of the oxidized collagen to interact normally with platelets (10,11).…”
mentioning
confidence: 99%